Record of Mechanitis polymnia (Lepidoptera: Ithomiinae) on Solanum jamaicense and life cycle in the laboratory - GIRALDO-S., CARLOS EDUARDO; URIBE-S., SANDRA I. (Revista Colombiana de Entomología, 2010)
Immature stages of the butterfly Mechanitis polymnia (Lepidoptera: Ithomiinae) were collected on Solanum jamaicense in six localities of the western and central ranges of the Colombian Andes, from the departments of Antioquia and Caldas. Observations on the oviposition habits of the females were made in the field. Notes were made on the morphology, development and behavior of the immatures stages, and the life cycle under laboratory conditions is described.